Mapping Misconceptions in Heat and Temperature: Rasch Analysis of Four-Tier Diagnostic Responses - Roziqin Roziqin; Achmad Samsudin; Duden Saepuzaman; Ida Kaniawati; Mimin Iryanti; Nor Farahwahidah Abdul Rahman (Jurnal Pendidikan MIPA, 2026)
Understanding of heat and temperature has been a major obstacle in students' learning of thermodynamics, but many diagnostic studies still report descriptive data on the frequencies of students' responses, which lack evidence about the psychometric quality of the measurement, the ranking of items, and the validity of the response patterns. This paper aims to address this by combining a four-tier diagnostic test with the Rasch Partial Credit Model (PCM) to assess Grade XII students' conceptual knowledge of heat and temperature and to evaluate the diagnostic test's psychometric quality. We surveyed 60 senior high school students in Bandung, Indonesia, using a quantitative approach. They responded to a diagnostic test with four-tiered items on the concepts of temperature, thermal expansion, heating effect on temperature, states of matter, and heat transfer. We classified these responses into conceptual categories and applied Rasch-PCM to assess reliability, item and person fit, unidimensionality, category functioning, gender-based differential item functioning (DIF), Wright map, and the match between difficulty and ability. The findings show the instrument had satisfactory psychometric characteristics, including a reliable hierarchy of item difficulty, acceptable fit to the model, essential unidimensionality, and mostly well-functioning response categories. There was little evidence of measurement bias as items functioned similarly for both males and females. The diagnostic map indicated that students' concepts were characterized by partial understanding and misunderstanding, and by ongoing confusion among heat, temperature, and thermal energy. The most challenging concepts were density change upon heating, convection, thermal expansion on the particle level, thermal feelings, and mechanisms of heat transfer. The person-fit and scalogram analyses also showed irregular response patterns of a minority group of students, suggesting a potential for guessing, disjointed reasoning, or unstable understanding. These findings show that the use of four-tier diagnostic responses with Rasch-PCM offers a higher-standard approach to identifying misconception structures than descriptive diagnostic analysis. Keywords: student misconceptions, four-tier diagnostic, rasch analysis, heat, temperature.